2019
DOI: 10.1016/j.nima.2019.162602
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient isotope separation and ion implantation of  163Ho for the ECHo project

Abstract: The effective electron neutrino mass measurement at the ECHo experiment requires high purity 163 Ho, which is ion implanted into detector absorbers. To meet the project specifications in efficiency and purity, the entire process chain of ionization, isotope separation, and implantation of 163 Ho was optimized. A new two-step resonant laser ionization scheme was established at the 30 kV magnetic mass separator RISIKO. This achieved ionization and separation efficiencies with an average of 69(5) stat (4) sys % u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…139 La 16 O, 155 Gd) or radioactive ( 155 Eu) impurities [11]. Similar conditions were observed for the shorter-lived isotope 149 Tb, also produced at ISOLDE, where isobaric contaminants 149 Eu and 133 Ce 16 O are limiting the sample purity [12]. Furthermore, the separation technique was developed to extract minute quantities of radioisotopes.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…139 La 16 O, 155 Gd) or radioactive ( 155 Eu) impurities [11]. Similar conditions were observed for the shorter-lived isotope 149 Tb, also produced at ISOLDE, where isobaric contaminants 149 Eu and 133 Ce 16 O are limiting the sample purity [12]. Furthermore, the separation technique was developed to extract minute quantities of radioisotopes.…”
Section: Introductionmentioning
confidence: 71%
“…For instance, it was demonstrated that 139 Ce 16 O was present during the extraction of 155 Tb, produced at ISOLDE by irradiation of a tantalum target with high energy proton beam. 139 Ce 16 O is a thermally ionized isobaric contaminant and is not separated from 155 Tb in the electromagnet. The same concern exists for other stable (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activities produced were sufficient to perform one preliminary in vitro assay. Previously, ionization efficiency values in the order of 20–50% (on mass separators equipped with laser ion sources) were reported for holmium, dysprosium and lutetium ( 38 , 43 , 44 ). Similar results were also obtained at the CERN-MEDICIS facility for 167 Tm ( 45 ), indicating room for separation efficiency improvements for 169 Er.…”
Section: Introductionmentioning
confidence: 99%
“…A mass separation step is added in between to assure high purity of the 163 Ho and remove unwanted ionized species. This approach is used in ECHo and is also foreseen for HOLMES with some differences in the technological realization and, in particular, in the ion source [16,17].…”
Section: Introductionmentioning
confidence: 99%